Mechanisms of autoimmunity in the non‐obese diabetic mouse: effector/regulatory cell equilibrium during peak inflammation. Issue 4 (8th February 2016) - Askenasy, Nadir
Summary: Immune imbalance in autoimmune disorders such as type 1 diabetes may originate from aberrant activities of effector cells or dysfunction of suppressor cells. All possible defective mechanisms have been proposed for diabetes‐prone species: (i) quantitative dominance of diabetogenic cells and decreased numbers of regulatory T cells, (ii) excessive aggression of effectors and defective function of suppressors, (iii) perturbed interaction between effector and suppressor cells, and (iv) variations in sensitivity to negative regulation. The experimental evidence available to date presents conflicting information on these mechanisms, with identification of perturbed equilibrium on the one hand and negation of critical role of each mechanism in propagation of diabetic autoimmunity on the other hand. In our analysis, there is no evidence that inherent abnormalities in numbers and function of effector and suppressor T cells are responsible for the immune imbalance responsible for propagation of type 1 diabetes as a chronic inflammatory process. Possibly, the experimental tools for investigation of these features of immune activity are still underdeveloped and lack sufficient resolution, in the presence of the extensive biological viability and functional versatility of effector and suppressor elements.